RANCANG BANGUN KOTAK PENYIMPAN IKAN BERINSULASI UNTUK MEMPERTAHANKAN KUALITAS IKAN DENGAN PROSES PENDINGINAN SERTA APLIKASINYA PADA IKAN TONGKOL (AUXIS THAZARD) - Margaretha Tuti Susanti; Parhimpunan Purba (TEKNIK, 2008)
Fish Cooler Box Have Designed With Measurement 50 X 70 X 40 Cm, with layers box wall and the partfrom out box : fiber glass, strerofoam wood and fiber glass. The boxes will be aplicate for tongkol fish(Auxis thazard) preservation. Variation that done in this research is comparation between ice and fish.topreservation times. Parameter that measured are fish quality like : fat degradation with TMA method,protein degradation with TVB method, rotten with TMAO method, and organoleptic test like : smell,appearence, texture. Result of this research with that parameter tests are : comparation between ice andfish 2:1, but with comparation 1:1 fish quality is still good for consumption